Pengaruh Manajemen Modal Kerja, Umur Perusahaan, Ukuran Perusahaan, Dan Pertumbuhan Penjualan Terhadap Profitabilitas (Studi Kasus Pada Perusahaan Food And Beverage Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2018) - Sari Oktavia; Rois Arifin; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractFinancial aspect is a measure of a company's success in its performance and one of the aspects that influences the company's survival. Companies that have healthy financial performance will be known from how the company's ability to obtain profits through profitability ratios. This study aims to determine and analyze the effect of working capital management, company age, company size, and sales growth on profitability of companies listed on the IDX. The data collection method used in this study is documentation. The type of data used in this study is secondary data. the method of analysis used in this study is multiple regression. This study uses data from companies listed on the Indonesia Stock Exchange in 2016-2018 and samples were taken using purposive sampling. The number of samples taken in this study were 10 companies. The results of this study are the Working Capital Management and Age of the company affect the profitability, and the variable size of the company and growth does not affect the profitability. Keywords: Working Capital Management, Company Age, Company Size, Profitability.